2018
DOI: 10.1016/j.molliq.2018.07.123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CaO(MgO) on the structure and properties of aluminosilicate system by molecular dynamics simulation

Abstract: The effect of CaO(MgO) on the structure and properties of aluminosilicate system by molecular dynamics simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 38 publications
2
20
0
1
Order By: Relevance
“…This observation for CMAS glass is inconsistent with silicate mineral dissolution experiments which generally show that the dissolution rate of dimagnesium silicate is several orders in magnitude lower than that of dicalcium silicate [31,32]. The different impact Ca and Mg atoms have on the reactivity of silicate glasses and minerals could be associated with the formation of highly reactive free oxygen (FO) sites in CMAS glasses (not present in common silicate minerals), which seem to be promoted by Mg atoms [33,34].…”
Section: /47mentioning
confidence: 66%
See 1 more Smart Citation
“…This observation for CMAS glass is inconsistent with silicate mineral dissolution experiments which generally show that the dissolution rate of dimagnesium silicate is several orders in magnitude lower than that of dicalcium silicate [31,32]. The different impact Ca and Mg atoms have on the reactivity of silicate glasses and minerals could be associated with the formation of highly reactive free oxygen (FO) sites in CMAS glasses (not present in common silicate minerals), which seem to be promoted by Mg atoms [33,34].…”
Section: /47mentioning
confidence: 66%
“…Although it is challenging to obtain structural information on amorphous aluminosilicates, several experimental techniques have been shown to be extremely valuable, including nuclear magnetic resonance (NMR) [15,40,41], and X-ray and neutron total scattering [7,33,[42][43][44]. On the other hand, atomistic modeling techniques, including force fieldbased molecular dynamics (MD) simulations [34,43,45,46] and quantum mechanics-based density functional theory (DFT) calculations [47,48], have been successfully used to generate detailed and realistic structural representations for aluminosilicate glasses, including when combined with X-ray and neutron scattering experiments [33]. Furthermore, MD simulations have been recently employed in the glass community to derive structural information that connects glass composition and molecular features to glass properties, including Young's modulus, density, viscosity, glass transition temperature, and leaching and chemical durability [49].…”
Section: /47mentioning
confidence: 99%
“…Moreover, a recent study on CAS and MAS melts (at 1773 K) showed that the MAS melt has a much higher FO content than the corresponding CAS melt for the same amount of modifiers (i.e., Mg or Ca). 55 These results suggest that the presence of Mg in CMAS glass promotes the formation of FO, which is a contributing factor to the underestimation of the NBO content in the simulation as compared to the simple stoichiometric calculation (as shown in Table 4). This preferential association of Mg atoms with FO sites also explains the higher Ca/Mg ratios around Si and Al atoms within their first coordination shell as compared to the average Ca/Mg compositional ratio in the CMAS glass (Figure 7 and Table 3).…”
Section: Oxygen Environmentmentioning
confidence: 79%
“…Computational tools such as ab initio and force-field molecular dynamics (MD) simulations have been used to predict glass structures, uncovering important structural details that are difficult to obtain solely with experiments. Specifically, force-field MD simulations have been widely used to predict the structure and properties of various silicate glasses and melts, including CAS 7,27,28,[30][31][32][33]54 and CMAS 38,[55][56][57][58][59] glass systems. A key advantage of force-field MD simulations compared with those based on ab initio MD is their relatively high computational efficiency, however, the accuracy of these simulations is highly dependent on the accuracy of the chosen force-field for the material in question 31 , where the force-field is developed typically by refining the force-field parameters against limited experimental data and/or ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies have focused on the macroscopic properties of refining slag, including viscosity and melting temperature [18,19]. Changes in microstructure are directly related to variation of the macroscopic properties [20,21]. High temperatures in the smelting process make it difficult to detect the structure and properties of the slag.…”
Section: Introductionmentioning
confidence: 99%